MEASUREMENT OF ROOT LENGTH DENSITY IN INTACT SAMPLES USING X-RADIOGRAPHY AND IMAGE ANALYSIS - Pierret, Alain; Moran, Chris J; Mclachlan, Colin B; Kirby, John M (Image Analysis and Stereology, 2011)
Measurement of root system attributes is of critical importance to understand and model plant growth. Root length density, the length of roots per unit volume of soil, is one of the important parameters required to understand plant performance. Measuring techniques currently in use to assess this parameter, such as for example core washing, are notoriously imprecise and labour-intensive. Roots and soil being inextricably linked, it is virtually impossible to separate them without loosing a significant amount of the root sample to be measured. This noticeably compromises the accuracy of washing techniques. For this reason, non-invasive measurement approaches are highly desirable. Here, a method based on the combination of X-radiography and image analysis is proposed as a new alternative for the measurement of root length density from intact samples. The successive steps of the method, from sampling to image acquisition are briefly described. A specific measurement algorithm, designed to account for the complex spatial arrangement of the roots within the samples is then presented and discussed in detail.